IMF Staff papers : Volume 22 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1975)
In this paper it is argued that in a system of widespread managed floating, as in a par value system with occasional floating, the problem of asymmetry of adjustment between the issuers of the principal intervention currencies and other countries and the problem of ensuring an effective international management of reserves remain to be solved. If the latter problem is less acute under a floating system, the former problem is potentially more acute than under par values. Although widespread floating would appear to offer no obstacle to the operation of a substitution account, its effect on the acceptability of asset settlement is debatable and it would add considerably to the difficulties of organizing multicurrency intervention. If politically acceptable, a system of guided intervention oriented to an established system of normal exchange rate zones would probably be superior to any other arrangement under floating for the purpose of promoting symmetry in adjustment, while permitting an adequate degree of exchange rate management and avoiding the anomaly of mutually offsetting intervention.